Diverse Scripts, Same Mistakes: Identifying Common Pitfalls in the Typographic Designs of Indonesian Traditional Scripts - Aditya Bayu Perdana (Jurnal Desain Komunikasi Visual Nirmana, 2024)
The writing traditions of Indonesia are characterized by scriptural diversity, although today most of the traditional scripts have been supplanted by Latin in everyday use. There are revitalization efforts and design attempts to use these scripts in more contemporary settings. However, many efforts suffered from substandard typographic quality that does not represent the inherent nature or design spirit of authentic materials. To better understand and problematize this phenomenon, this study conducts historical and literature review using qualitative methods. The typographic quality of some key materials is described and presented in chronological order to show how flawed representation in some materials seem to be perpetuated into contemporary design. A review of archival materials from the 20th century onward reveals that a drop in typographic quality happens concurrently with the disappearance of traditional script from everyday use. The public’s unfamiliarity with traditional scripts was then exacerbated by flawed representation in secondary material references published privately and by the government alike throughout the 1980s to the early 2000s. Notwithstanding their scholarly content, their representation of traditional scripts often shows typographic sloppiness that poorly represent normative and variant letterforms found in primary materials. Some contemporary designs pitfalls of traditional scripts can be traced to the uncritical over-reliance to these secondary materials, such as diacritic miniaturization and graphic stereotyping. There are some indications that typographic awareness and quality is improving in some communities in conjunction with increase of digital use and better access to primary materials. But whether this improvement proved sustainable in the long run remains to be seen. The author hopes that by identifying these pitfalls, future designers will pay more attention to typographic issues in Indonesian traditional scripts and can apply more informed design decisions that contribute to the revitalization of this heritage.